Kartography - Shamsie, Kamila (Bloomsbury Publishing, 2018)
"Crib mates, raised together from birth, narrator Raheen and her best friend Karim dream each other's dreams, finish each other's sentences, speak in a language of anagrams. They share an idyllic childhood in upper-class Karachi with parents who are also best friends. The two couples were even once engaged to the opposite partner until they rematched in what they jokingly call "the fiancee swap." The night Karim's family migrates from Karachi to London, Raheen knows that "some of my tears were his tears and some of his tears were mine."" "But as distance and adolescence split them apart, Karim takes refuge in the rationality of maps while Raheen tries to hide from the secret behind her parents' exchange. When she finally does face the truth it takes us back two decades to reveal a story not just of a family's turbulent history but that of a country - and brings us forward to a grown-up Raheen and Karim poised between strained friendship and fated love."